Chemical constituents from the roots of Fallopia convolvulus (L.) A. Löve. (June 2019) - Li, Keming; Zhang, Zhongxin; Zhao, Guoliang; Sun, Ping; Cui, Bingbing; Chi, Shumei
Abstract: Twenty compounds, including three sterols (1 –3 ), three phenols (4, 14 and15 ), four anthraquinones (5, 7, 8 and16 ), one chromone (6 ), two stilbenes (9 and10 ), three amides (11 –13 ), three flavonoids (17 –19 ) and one organic acid (20 ), were obtained by modern phytochemical isolation methods. Their structures were identified by spectroscopic methods and in comparison with the published data in the references. Among them, compound2, 3, 11 and13 were firstly discovered from genus Fallopia, and compounds1, 5 –8, 10, 14, 15, 17, 19 and20 were obtained from F. convolvulus for the first time. The chemotaxonomic significance of these compounds was also discussed, which revealed the relationships between F. convolvulus and some other species of Polygonaceae family. Highlights: We studied the chemical constituents of Fallopia convolvulus (L.) A. Löve. Twenty compounds were obtained from this species, and were identified by spectroscopic methods and data comparison. Four compounds were firstly isolated from genus Fallopia, eleven were obtained from this species for the first time. The obtained constituents might reveal the relationships between F. convolvulus and some other plants of Polygonaceae.